2018
DOI: 10.1186/s12879-018-3349-5
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of extrapulmonary tuberculosis presenting as fever of unknown origin in an intermediate-burden country

Abstract: BackgroundTuberculosis (TB), especially extrapulmonary tuberculosis (EPTB), is an important cause of fever of unknown origin (FUO) in TB-burdened areas. Little information is known about patients with EPTB with clinical features presenting as FUO and about the factor of delaying the diagnosis.MethodsWe retrospectively analyzed EPTB patients who were referred with FUO at 3 university-affiliated hospitals over 8 years (2010–2017). The subjects were assigned to groups of early diagnosis and delayed diagnosis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
3
14
1
Order By: Relevance
“…[3,5,23] EPTB disease site was not recorded in 8.5% of patients included in the study. In TB-burdened countries EPTB is one of the important causes of fever of unknown origin [34]. In TB registers where disease site was recorded for majority of the notified EPTB cases, one plausible explanation for missing details is, that these patients were most likely initiated on empiric TB treatment for fever of unknown origin without further investigations either due to lack of diagnostic facilities or resources.…”
Section: Plos Onementioning
confidence: 99%
“…[3,5,23] EPTB disease site was not recorded in 8.5% of patients included in the study. In TB-burdened countries EPTB is one of the important causes of fever of unknown origin [34]. In TB registers where disease site was recorded for majority of the notified EPTB cases, one plausible explanation for missing details is, that these patients were most likely initiated on empiric TB treatment for fever of unknown origin without further investigations either due to lack of diagnostic facilities or resources.…”
Section: Plos Onementioning
confidence: 99%
“…Tuberculosis presenting as FUO can be difficult to diagnose due to commonly nonspecific signs and symptoms [25,32,33]. This study found high positive predictive value and high likelihood ratio of a positive test for previous tuberculosis or tuberculosis exposure in the infectious category.…”
Section: Discussionmentioning
confidence: 63%
“…Despite the existence of guidelines for the diagnosis and treatment of TB [ 10 ], there tend to be cases of EPTB that present with atypical manifestations such as local pain, weight loss, night sweat and fever, which make the diagnosis difficult [ 11 ]. In addition, the anatomical sites frequently involves in EPTB are not easily accessible and require invasive procedures for diagnostic confirmation.…”
Section: Introductionmentioning
confidence: 99%